Laporan Baru Tentang Dacus longicornis dan Dacus petioliforma (Diptera:Tephritidae) di Daerah Istimewa Yogyakarta - Suputa Suputa; Edhi Martono; Dwi Hastuti Handayani; Rina Ediati (Universitas Gadjah Mada, 2004)
Research was conducted in Jogjakarta from April to October 2004, to know the existence and description of Dacus spp, in Indonesia especially in Jogjakarta Special Province: The result of the exploration shows that there are two species of Dacus spp. attracted to cue lure traps. The species are Dacus (Callantra) longicornis and Dacus (Callantra) petioliforma with characteristics as follows: notopleuron and mesopleural stripe are brownish on D. longicornis and yellow on D. petioliforma; mesonotum uniformly red-brown with midline dark marking and a small yellowish spot present on D. petioliforma and absent on D. longicomis; apical scutellum is brown fulvous on D. longicomis and yellow on D. petioliforma, on both of them are broad black fulvous on basal band.